2009
DOI: 10.1016/j.mam.2008.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Environmental toxicity, redox signaling and lung inflammation: The role of glutathione

Abstract: Glutathione (γ-glutamyl-cysteinyl-glycine, GSH) is the most abundant intracellular antioxidant thiol and is central to redox defense during oxidative stress. GSH metabolism is tightly regulated and has been implicated in redox signaling and also in protection against environmental oxidant-mediated injury. Changes in the ratio of the reduced and disulfide form (GSH/GSSG) can affect signaling pathways that participate in a broad array of physiological responses from cell proliferation, autophagy and apoptosis to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
203
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 292 publications
(216 citation statements)
references
References 157 publications
(202 reference statements)
11
203
0
2
Order By: Relevance
“…30 ROS and RNS play important roles in regulating cell survival, and a sudden excessive and prolonged surge of ROS/RNS could induce cell death. 31 In most tissues, the first line of defense against oxidative stress is the endogenous antioxidant defense system such as SODs: SOD1 in the cytoplasm, SOD2 in mitochondria, and SOD3 in the extracellular space. 32 Furthermore, free radical insult might activate PARP and culminate in an apoptotic cascade.…”
Section: Discussionmentioning
confidence: 99%
“…30 ROS and RNS play important roles in regulating cell survival, and a sudden excessive and prolonged surge of ROS/RNS could induce cell death. 31 In most tissues, the first line of defense against oxidative stress is the endogenous antioxidant defense system such as SODs: SOD1 in the cytoplasm, SOD2 in mitochondria, and SOD3 in the extracellular space. 32 Furthermore, free radical insult might activate PARP and culminate in an apoptotic cascade.…”
Section: Discussionmentioning
confidence: 99%
“…Effects of FP and CARB on GSH expression in bronchial epithelial cells GSH is one of the most important defensive mechanisms against oxidative stress (Biswas and Rahman 2009;Ghezzi 2011). The effect of CARB and FP on GSH expression in CSE-stimulated bronchial epithelial cells was explored.…”
Section: Effects Of Fp and Carb On Ros Formation In Bronchial Epithelmentioning
confidence: 99%
“…S-CMC-Lys has an antioxidant action that leads to a significant increase of glutathione (GSH) flux through the cell membrane (Guizzardi et al, 2006;Garavaglia et al, 2008). Such an increase in intracellular GSH induces a reduction in inflammatory cytokine release through inhibition of NFkB activation (Aoki et al, 1996;Antonicelli et al, 2002;Biswas & Rahman, 2009). A previous study reported that the pyrrolidine derivative pyrrolidine dithiocarbamate, an NFkB inhibitor, reduces acid-induced S. pneumoniae adherence to A549 cells via inhibition of PAFR induction (Ishizuka et al, 2001).…”
Section: Resultsmentioning
confidence: 99%